Modern methods of ablation of malignant tumors of the liver - L. I. Moskvicheva; D. V. Sidorov; M. V. Lozhkin; L. O. Petrov; M. V. Zabelin (Исследования и практика в медицине, 2018)
The purpose of this review is to demonstrate the possibility of performing various methods of thermal and non-thermal ablation in patients with primary and metastatic liver tumors on the basis of data available in the world medical literature.As conservative variants of local action in patients with non-resectable primary and secondary liver tumors and inoperable patients, various ablative techniques have been developed and used to achieve local control over the disease and increase the life expectancy of this group of patients. These include: radiofrequency ablation, microwave ablation, HIFU therapy, laser ablation, cryotherapy, chemical destruction of the tumor, irreversible electroporation, stereotactic radiation therapy.The effectiveness of these ablation methods depends on the size and localization of the tumor focus, and for thermal techniques — also on its location relative to large vessels. Ablative techniques have the maximum efficiency (in some cases, similar to surgical intervention) when exposed to early forms of primary cancer or secondary tumor formation of the liver in the presence of a solitary node with a maximum size up to 5 cm or 3 and less foci size up to 3 cm. The effectiveness of local destruction of tumor formations of the liver of larger diameter is increased by carrying out ablation by the second stage after performing chemoembolization of the hepatic artery or by combining various techniques of local action.The use of various modern methods of ablation of solid primary and secondary liver tumors in medical practice can expand the possibilities of antitumor treatment of this category of patients.